Pengaruh Pelatihan Job Crafting Terhadap Kebosanan Perawat Milenial Rumah Sakit X - Maulidina Hanun; Yunitasanti, Reny (Jurnal Studia Insania, 2025)
This study examines the effect of job crafting training on job boredom among nurses at X Hospital. This topic is crucial given that high levels of job boredom can impair performance and the quality of healthcare services. We hypothesized that job crafting training would significantly reduce job boredom. A quasi-experimental design with pre-test and post-test control groups was employed. Participants were randomly assigned to an experimental group (EG) or a control group (CG). The instruments included a boredom scale (α = 0.799) and a job crafting scale (α = 0.949). Hypothesis testing using the Mann-Whitney and Wilcoxon tests revealed a significant reduction in boredom levels after training (Z = –2.678, p = 0.007; p < 0.05). The mean post-training boredom score for the experimental group (5.80) was substantially lower than that of the control group (15.20). These findings confirm that job crafting training is an effective intervention for reducing job boredom. Results further suggest its value as a psychological strategy to enhance nurses’ well-being and support proactive approaches in industrial and organizational psychology.